Social Services Programs Today and in the Future - Vareikytė, Audronė (Socialinė teorija, empirija, politika ir praktika, 2001)
The development of social services is discussed in the paper. The institutional care system was dominating for a long time in Lithuania. The community-based social services are a new thing for social service users, providers and organizers. The different amount of resources is given to social services in municipalities. Almost 60 percent of social service fund is dedicated to institutional care and there is a tendency to increase the funding of institutional care. The childcare is mostly institutionalised. The social service system has to be directed towards the efficiency of the system, the involvement of private organizations and NGO into the provision of social services, the priority of community based services.